Modernisasi dalam Perspektif Samuel P. Huntington - Alamsyah Alamsyah; Syarifuddin Syarifuddin (SINTHOP: Media Kajian Pendidikan, Agama, Sosial dan Budaya, 2022)
This article describes the social and cultural changes in human life that are moving toward modernity. Today's social scientists seem concerned about modernization but tend to use Western industry as a reference for modern models. As Donald Eugene Smith assumed, the world has experienced "the grand process of modernization," considering secularization to be a certain and absolute modern condition. The most fundamental issue is that secularism is required to achieve modernity. As for the question, here is how the concept of modernization appears in the view of Samuel P. Huntington. Huntington is one of the American political experts who contributed to modernization studies. According to Huntington, modernization is a process of change that cannot be avoided. This is due to the growing development of science and technology, which also influences people's mindsets, attitudes, and values in various aspects of life. There are three reactions that arise from modernization theory, namely, first, rejecting both modernization and westernization, second, accepting both, and third, accepting the first and rejecting the second. From these three reactions, Huntington tends to see that modernization does not mean westernization. Because non-Western societies that are changing seem to be increasingly maintaining their own culture, even as they adopt Western values, institutions, and practices, without abandoning their own culture. Abstrak Artikel ini menjelaskan perubahan-perubahan sosial dan budaya kehidupan manusia yang bergerak menuju modern. Ilmuan sosial dewasa ini tampak terlihat prihatin terhadap modernisasi, tetapi cenderung menggunakan industri Barat sebagai acuan model modern. Sebagaimana asumsi Donald Eugene Smith, dunia telah mengalami The Grand Process of Modernization, menganggap sekularisasi pasti terjadi dan mutlak sebagai sarat modern. Masalah yang paling pokok, adanya keharusan bersikap sekuler untuk mencapai modernitas. Adapun yang menjadi pertanyaan di sini adalah bagaimana konsep modernisasi dalam pandangan Samuel P. Huntington. Menurut Huntington, modernisasi adalah sebuah proses perubahan yang tidak dapat terelakkan. Hal ini terjadi akibat semakin berkembangnya ilmu pengetahuan dan teknologi yang turut mempengaruhi pola pikir, sikap, nilai-nilai perilaku masyarakat dalam berbagai sisi kehidupan. Ada tiga reaksi yang muncul dari teori modernisasi, yaitu; pertama. menolak modernisasi maupun westernisasi, kedua, menerima keduanya, ketiga, menerima yang pertama dan menolak yang kedua. Dari ketiga reaksi ini, Huntington cenderung memandang modernisasi tidak berarti westernisasi. Karena, masyarakat-masyarakat non-Barat yang sedang berubah tampak semakin mempertahankan budaya sendiri, sekalipun mengadopsi nilai-nilai, institusi-institusi dan praktik-praktik Barat tetapi tidak meninggalkan kebudayaan sendiri.